Ambroxol for the treatment of COVID-19 among hospitalized patients: A multicenter retrospective cohort study - Lu, Yun; Yang, Qing-qing; Zhuo, Lin; Yang, Kun; Kou, Hao; Gao, Su-yu; Hu, Wen; Jiang, Qiao-li; Li, Wen-jing; Wu, Dong-fang; Sun, Feng; Cheng, Hong; et al. (Frontiers in Microbiology, 2022)
Ambroxol is a commonly used mucolytic agent principally used to treat respiratory diseases, which may have a role as adjunctive therapy for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection, but there is lack of evidence about its effectiveness on coronavirus disease 2019 (COVID-19) patients. To study the association between ambroxol use and clinical outcomes among hospitalized patients of COVID-19 infection. We conducted a multicenter retrospective cohort study involving 3111 patients with confirmed SARS-CoV-2 infection from three hospitals in Wuhan from December 19, 2019 to April 15, 2020 and the primary outcome was in-hospital mortality. COVID-19 patients were classified into ambroxol and non-ambroxol groups based on the administration of ambroxol during hospitalization. Two analyses including propensity score matching (PSM) to obtain a 1:1 balanced cohort and logistic regression were used to control for confounding factors. The average age of 3111 patients was 57.55±14.93 years old, 127 of them died during hospitalization, and 924 of them used ambroxol. Treatment with ambroxol did not have a significant effect on in-hospital mortality of COVID-19 patients when compared with non-ambroxol in PSM model after adjusting for confounders (8.0% vs. 3.5%, adjusted OR, 1.03 [95% CI, 0.54-1.97], p=0.936). Adverse events such as nausea/vomiting, headache, and rash were comparable between the two groups. Our results suggest that the use of ambroxol is not significantly associated with in-hospital mortality in COVID-19 patients, which provides evidence for evaluating the effects of ambroxol on COVID-19 patient outcomes and may be helpful for physicians considering medication alternatives for COVID-19 patients.